Uma abordagem para o desenvolvimento de um sistema de informação para projeto, implantação e gerência de cadeias logísticas de manutenção de sistemas técnicos - Côrtes, André Luís de Almeida (2006)
This work aim is to suggest an approach for the development of information systems for the project, deployment and management of maintenance logistics chains. It describes how a technical system logistic chain is structured and works. It contains a survey of several international standards that supports the development of Product Data Managment (PDM) information systems, showing the actual trend of systems that talk to each other in order to allow a better interoperability among of databases of technical systems belonging to the same field of actinty. It uses the logistic support analysis process as a source to suggest the data that must be contained in the information system. Based on this data a preliminary conceptual model was developed using UML, showing how this approach can be used for the development of an information system.